2020
DOI: 10.1021/acsphotonics.0c00225
|View full text |Cite
|
Sign up to set email alerts
|

Tuning Plasmonic Coupling from Capacitive to Conductive Regimes via Atomic Control of Dielectric Spacing

Abstract: The gap length between plasmonic nanoparticles determines the strength of the optical coupling that results in electromagnetic field enhancement for spectroscopic and other applications. Although gap plasmon resonances have been the focus of increasing research interest, experimental observations have primarily been limited to the coupling of spherical nanoparticles that may not provide clear spectral contrast of the optical response as the interaction evolves from capacitive to charge transfer with the gap si… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
29
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(31 citation statements)
references
References 51 publications
(102 reference statements)
2
29
0
Order By: Relevance
“…These findings introduce optical-field-driven electronic dynamics to nanoscale structures, allowing us to optically modulate the single-electron transport in well-designed nanoplasmonic structures; in turn, this enables ultrafast nonlinear control of matter at the atomic scale, single-molecule orbital imaging at terahertz operating frequencies, and atomic-scale devices. [131][132][133][134][135] The air gap should be filled with atomically layered films (e.g., Al 2 O 3 , [123] shown in Figure 4g) to investigate quantum tunneling, and it can be further studied in molecules, 2D materials, excitons, and active materials, as described in the following sections.…”
Section: Air/vacuum/thin Film Gapmentioning
confidence: 99%
See 1 more Smart Citation
“…These findings introduce optical-field-driven electronic dynamics to nanoscale structures, allowing us to optically modulate the single-electron transport in well-designed nanoplasmonic structures; in turn, this enables ultrafast nonlinear control of matter at the atomic scale, single-molecule orbital imaging at terahertz operating frequencies, and atomic-scale devices. [131][132][133][134][135] The air gap should be filled with atomically layered films (e.g., Al 2 O 3 , [123] shown in Figure 4g) to investigate quantum tunneling, and it can be further studied in molecules, 2D materials, excitons, and active materials, as described in the following sections.…”
Section: Air/vacuum/thin Film Gapmentioning
confidence: 99%
“…g) Quantum energy transport in the nanorod-on-film structure with Al 2 O 3 film. Reproduced with permission [123]. Copyright 2020, American Chemical Society.…”
mentioning
confidence: 99%
“…Because of the strong confinement of the optical field, the coupling between the charge oscillations in a metal nanoparticle and the image charges in a nearby mirror film has attracted considerable attention in numerous applications ranging from metamaterials to photocatalysis to plasmonic sensing. To date, to create a tiny cavity between the metal nanoparticle and metal film, it is essential to have a spacer layer that separates them in proximity. For example, nonmetal thin layers of either SiO 2 , semiconductors, or self-assembled monolayers are deposited onto a gold film, and thereafter, gold nanoparticles are placed on top of the nonmetal layer. Alternatively, gold nanoparticles fully coated with either SiO 2 or organic molecules can be introduced onto a gold film. In either case, the nanocavities are produced as occupied by the spacer layers. Consequently, it is evident that the molecules in surrounding media are unable to diffuse into the nanocavity, where the optical field is significantly enhanced.…”
mentioning
confidence: 99%
“…To further characterize the single particles using the two different illumination mechanisms, we plot the full width at half-maximum (fwhm) for each of the different peaks shown in Figure S3. The peak at 637 nm in RDF and the peak at 646 nm in TIRS, having a similar fwhm, are believed to correspond to a charge transfer, out-of-plane coupling mode. , …”
Section: Resultsmentioning
confidence: 96%
“…This single peak is known as a charge transfer plasmon, which was found to be independent of the nanorod aspect ratio . A further study demonstrated additional plasmon coupling modes, resulting from cavity plasmons, when AuNRs were placed a few angstroms from the gold film with a dielectric spacer …”
Section: Introductionmentioning
confidence: 91%